2020
DOI: 10.1002/jsfa.10263
|View full text |Cite
|
Sign up to set email alerts
|

Formation and migration of α‐dicarbonyl compounds during storage and reheating of a sugary food simulation system

Abstract: BACKGROUND The thermal processing of food results in the formation of α‐dicarbonyl compounds (α‐DCs) such as glyoxal (GO), methylglyoxal (MGO), 2,3‐butanedione (2,3‐BD), and 3‐deoxyglucosone (3‐DG), which are precursors of potentially harmful advanced glycation end products. Some of the α‐DCs found in food products might result from chemical deterioration reactions during storage and reheating. A range of sugary food simulation systems were stored at three different temperatures (4, 25, and 37 °C) and reheated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…After α-DCs of oils is captured using o-PDA during thermal treatment, derivatives were determined using a high-performance liquid chromatography-mass spectrometer (HPLC-MS, Agilent 1200 LC/MSD-Trap-XCT system, Agilent Technologies, Santa Clara, CA, USA) as previously reported ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…After α-DCs of oils is captured using o-PDA during thermal treatment, derivatives were determined using a high-performance liquid chromatography-mass spectrometer (HPLC-MS, Agilent 1200 LC/MSD-Trap-XCT system, Agilent Technologies, Santa Clara, CA, USA) as previously reported ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the field of food, studies have found that microwave processing may produce toxic substances in food starch, or make the structure change to expose some more potentially toxic sites [ 147 ]. For example, microwave heating will increase the content of α -dicarbonyl compounds, which lead to an increase in harmful glycosylation products [ 148 ]. And because of the oxidation effect of microwave, microwave cooking has higher levels of cholesterol oxides than other cooking methods, which can also have negative effects on human health [ 149 ].…”
Section: Safety Analysis Of Microwave Technology In Pharmaceutical Fieldmentioning
confidence: 99%
“…a-DCs could interact with the side-chain groups of arginine (Arg) and lysine (Lys) residues. Among all of the a-DCs, MGO exists the most widely in heat-processed foods ( Kim et al, 2021 , Wang et al, 2020 , Zheng et al, 2022 , Zhuang et al, 2020 ). MGO in fats and oils is also formed by lipid degradation during processing.…”
Section: Introductionmentioning
confidence: 99%